Physician Communication Regarding Cost When Prescribing Asthma Medication to Children - Patel, Minal R. (Clin Pediatr (Phila), 2009)
Children with asthma require multiple medications, and cost may be a barrier to care. The purpose of this study was to determine how often physicians ask about cost when prescribing new asthma medication and to identify factors influencing queries. We surveyed pediatricians and family physicians and asked whether they asked about cost when prescribing new asthma medication and if cost was a barrier to prescribing. One third of physicians (35%) reported that concern for cost to the family was a barrier to prescribing. Half reported not asking their patients about drug costs. Pediatricians were less likely to ask about cost (odds ratio [OR] = 0.43; 95% confidence interval [CI] = 0.20–0.92) when compared with family physicians. For every 10% increase in the number of privately insured patients, a physician was less likely to ask about cost (OR = 0.83; 95% CI = 0.74–0.94). Communication about medication costs should be included in childhood asthma management.